A Review on Banned Drugs - Vaishnavi S, Ghodake; Sachin, Hangargekar; Priyanka D, Yelkote; Mohini A, Gurav; Ayesha N, Siddique; Madhav, Honrao; Sante, Rohini; Madhuri., Phulari (Asian Journal of Pharmaceutical Research and Development, 2023)
India has become a hub for the availability and usage of banned or harmful medicines such as Nimesulide, D’cold, Novalgin, Lomofen, and Rofecoxib, among others. The decision to ban a drug is based on the risk versus benefit ratio evaluated through post-marketing surveillance and the Adverse Drug Reaction Reporting System. Pharmaceutical negligence among doctors can lead to hazardous effects on the general health of a patient. It is important for the government to spread information on drugsideeffects. The prescribing of drugs is an essential practice for medical professionals. In promoting a healthy lifestyle, the prevention of diseases is important, but equally important is treatment of such diseases with safe drugs. Every drug has some side effects, but with the correct dosage, it can be avoided. Banned drugs have more adverse/side effects. Drugs that are found unsafe in post-marketing surveillance are banned by regulatory authorities. The Drug Controller General of India (DCGI) is the highest authority in India to approve or ban a drug. Despite this, banned drugs are still available in developing countries such as India due to a lack of law enforcement, physician awareness, and drug control authorities failing to inform hospitals of the status of medicine. India is a major hub for banned drugs.